THE INFLUENCE OF PSYCHOLOGICAL EMPOWERMENT AND ISLAMIC SPIRITUAL LEADERSHIP ON ORGANIZATIONAL COMMITMENTS AND INTRINSIC MOTIVATION - Febrianto, Abi Sopyan; Noermijati, Noermijati; Juwita, Himmiyatul Amanah Jiwa; Alashkam, Sana Amer (Universitas Brawijaya, Indonesia, 2019)
This study aims at examining and analyzing the influence of psychological empowerment and Islamic spiritual leadership on intrinsic motivation and organizational commitment. Respondents in this study were administrators at the Campus Dawah Association in Brawijaya University, which total up to 166 respondents. The data were analyzed using Partial Least Square (PLS) with version 3.0 SmartPLS software. The study found that psychological empowerment and Islamic spiritual leadership have a significant effect on intrinsic motivation. Psychological empowerment, Islamic spiritual leadership, and intrinsic motivation have a significant effect on organizational commitment.Furthermore, intrinsic motivation can mediate the influence of psychological empowerment and Islamic spiritual leadership on organizational commitment. Future researchers may expand the scope of the discussion to the value of the organization